Ad-CD40L mobilizes CD4 T cells for the treatment of brainstem tumors. Issue 12 (27th May 2020) - Wongthida, Phonphimon; Schuelke, Matthew R; Driscoll, Christopher B; Kottke, Timothy; Thompson, Jill M; Tonne, Jason; Stone, Cathy; Huff, Amanda L; Wetmore, Cynthia; Davies, James A; Parker, Alan L; Evgin, Laura; et al.
Abstract: Background: Diffuse midline glioma, formerly DIPG (diffuse intrinsic pontine glioma), is the deadliest pediatric brainstem tumor with median survival of less than one year. Here, we investigated (i) whether direct delivery of adenovirus-expressing cluster of differentiation (CD)40 ligand (Ad-CD40L) to brainstem tumors would induce immune-mediated tumor clearance and (ii) if so, whether therapy would be associated with a manageable toxicity due to immune-mediated inflammation in the brainstem. Methods: Syngeneic gliomas in the brainstems of immunocompetent mice were treated with Ad-CD40L and survival, toxicity, and immune profiles determined. A clinically translatable vector, whose replication would be tightly restricted to tumor cells, rAd-Δ24-CD40L, was tested in human patient–derived diffuse midline gliomas and immunocompetent models. Results: Expression of Ad-CD40L restricted to brainstem gliomas by pre-infection induced complete rejection, associated with immune cell infiltration, of which CD4+ T cells were critical for therapy. Direct intratumoral injection of Ad-CD40L into established brainstem tumors improved survival and induced some complete cures but with some acute toxicity. RNA-sequencing analysis showed that Ad-CD40L therapy induced neuroinflammatory immune responses associated with interleukin (IL)-6, IL-1β, and tumor necrosis factor α. Therefore, to generate a vector whose replication, and transgene expression, would be tightly restricted to tumor cells, we constructed rAd-Δ24-CD40L, the backbone of which has already entered clinical trials for diffuse midline gliomas. Direct intratumoral injection of rAd-Δ24-CD40L, with systemic blockade of IL-6 and IL-1β, generated significant numbers of cures with readily manageable toxicity. Conclusions: Virus-mediated delivery of CD40L has the potential to be effective in treating diffuse midline gliomas without obligatory neuroinflammation-associated toxicity.